MRI Detection of Intratumoral Fat in Colorectal Liver Metastases after Preoperative Chemotherapy - Nakai , Yudai; Gonoi , Wataru; Hagiwara , Akifumi; Nishioka , Yujiro; Abe , Hiroyuki; Shindoh , Junichi (Seram, 2021)
OBJECTIVE: To investigate the incidence and clinical significance of intratumoral fat deposition in colorectal liver metastases (CLMs) after preoperative chemotherapy using dual-echo gradient-recalled echo MRI. MATERIALS AND METHODS: Our institutional review board approved this retrospective radiographic study and waived the requirement for informed patient consent. Fifty-nine patients (26 women; median age, 62 years) who underwent preoperative MRI and curative hepatic resection for CLMs after chemotherapy were selected. Twenty (20/59) patients also underwent MRI before MRI. On dual-echo gradient-recalled echo MR images, intratumoral fat deposition and fat signal fraction at the densest areas of fat deposition in CLMs were evaluated. Predictors of overall survival and intratumoral fat deposition after chemotherapy were identified by multivariate analyses. RESULTS: Before and after chemotherapy, none (0/20) and 54% (32/59) of the patients exhibited intratumoral fat deposition, respectively. Independent predictors of poor overall survival were: presence of ≥ 5 CLMs (p < .001); fat signal fraction ≥ 12% (p = .01); age ≥ 65 years (p = .02); and tumor response classified as progressive or stable disease by the Response Evaluation Criteria in Solid Tumors 1.1 (p = .049). Predictors of tumor fat signal fraction ≥ 12% after chemotherapy were: largest tumor size ≥ 5 cm (p = .005); tumor calcification (p = .008); and history of cetuximab or panitumumab administration (p = .04). CONCLUSION: Colorectal liver metastases after preoperative chemotherapy frequently exhibit intratumoral fat deposition.